IMPLEMENTASI POPSICLE STICK RANDOM CALLING UNTUK MENCIPTAKAN PELUANG YANG SAMA DALAM BERPARTISIPASI DAN TIDAK ADA DOMINASI SISWA PINTAR DI SMP N 4 PAKEM - Wulandari, Nidya Ferry; Hidayatullah, M Tamim; Ramadani, Iqbal (Department of Mathematics Education , University of Jember, 2021)
Students in SMP Negeri 4 Pakem have high-level participation and are very active when they learn in class. But we cannot ignore that there are some students that do not share their ideas or comment in front of the class. Based on observation, students’ participation is dominated by some students. That is why the objective of this study was to shed light on the implementation of the random calling technique using popsicle sticks to improve all of the students’ participation. The research was qualitative narrative research which has seventh-grade students in SMP Negeri 4 Pakem as the research subject. To collect the data used observation technique and questionnaire. The data collected was analyzed by using a descriptive technique based on data triangulation. The result of this study is that teacher and students make an agreement on how to implement random calling using popsicle sticks. This random calling technique is used after giving students an opportunity to be active in class voluntarily. Based on the questionnaire submitted, 75% of students agree that mathematics learning using random calling gives them a broad opportunity and they feel challenged in class.